Das Theater von Ephesos : archäologischer Befund, Funde und Chronologie - Akar-Tanriver, Duygu (Forschungen in Ephesos, 2017)
"This volume of the Forschungen in Ephesos presents the recent archaeological research at the theatre of Ephesus. Beside the results of the excavations the volume incorporates the analysis of the various find categories, such as pottery and glass, terracotta, sculptures, small finds and coins as well as archaeozoological and epigraphical finds. With this, the reader can comprehensively follow and review the chronology and the architectural development of the Ephesian monument. The construction started in the second quarter of the 2nd century BC and until the Byzantine period eight building or usage phases can be classified. A fundamental structural transformation can be attested during Flavian times. The building measures include in particular the renewal of the stage building with the erection of the magnificent three-storied scaenae frons, which due to a building inscription on the architrave of the lower story can be dated to the year 85 AD, as well as the erection of the Roman logeion, reaching far into the Hellenistic orchestra. The large-scale structural enhancement of the auditorium, through which the number of the possible audience rose to about 20.000, necessitated a new circulation and supply system in form of a monumental staircase in the south. The stairs gave access to three vaulted corridors leading to the three diazomata of the auditorium."--Publisher's website